Influencing Factors Business Success for Business People in the Era of Disruption - Ampa, Andi Tenri (International Journal of Asian Business and Management, 2023)
This research aims to analyze the factors that influence business success among business people in the era of disruption. In this era, rapid changes in technology, business models and consumer preferences have created an unstable and uncertain environment for business people. Through a comprehensive literature review, this research identifies several key factors that are relevant in the context of business success in the era of disruption. These factors include technological innovation and adaptation, managerial capabilities that are responsive to change, strong customer orientation, digital skills, and speed and flexibility in dealing with business changes. This research uses a qualitative descriptive method, a type of literature study which aims to describe the results of the researchers' findings on several journal articles found. The results of this research reveal that the factors that influence business success among business people in the era of disruption are interrelated and have a significant impact. Technological innovation and adaptation have proven to be important elements in creating competitive advantage. Apart from that, responsive managerial abilities, strong customer orientation, developed digital skills, and the ability to adapt to business changes quickly and flexibly are also key factors in achieving business success in the era of disruption. This research contributes to the understanding of the factors that influence business success among business people in the era of disruption